Modular cryogenic piezoelectric scanner for scanning SQUID microscopy - J. Bedard; J. Franklin; Z. Ritchey; M. Roshdy; O. R. Bilal; M. Jain; I. Sochnikov (AIP Advances)
Scanning superconducting quantum interference device (SQUID) microscopy is a powerful tool to study a wide variety of magnetic phenomena including weak magnetism originating from interfaces or antiferromagnets. Many SQUID microscopies utilize piezoelectric “s-bender” designs which offer large scan areas but can be sensitive to vibrations. Here, we design a new cryogenic scanner based off modular sets of double piezoelectric bimorphs which have higher resonant frequencies than “s-bender” designs while maintaining a 160 × 160 μm2 scan area. We demonstrate scanning capabilities by imaging local magnetic flux and susceptibility of an antiferromagnetic EuTiO3 thin film. This design provides extremely sensitive magnetic measurements and is readily adaptable for applications in other scanning probe techniques.